Design and Implementation of an FPGA-Based Digital Twin for an Electric Motor - Sarac, Mehmet Riza; Aydogmus, Omur (Springer Science and Business Media Deutschland GmbH, 2023)
This paper presented a development of a system that can emulate a real electric motor in real time. This system, called digital twin or real-time digital simulator (RTDS), has critical value for many applications. The digital twin was developed in the field-programmable gate array (FPGA) structure, which is a high-speed digital system for real-time operation. The motor model was rearranged so that it can be run in real time on the FPGA. The developed digital twin was operated together with the real motor under the same conditions. Both the armature currents and motor speeds of the two motors were examined instantaneously on the same scope screen. Digital twin motor results were achieved to be nearly identical to real motor results. Especially, the digital twin showed dynamics similar to real motor dynamics with high accuracy as expected for reference signals with very fast transitions. The latency of the developed system was measured as about It can be said that this latency is quite enough to emulate electric motors. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.
4th International Conference on Communication, Computing and Electronics Systems, ICCCES 2022 -- 15 September 2022 through 16 September 2022 -- Coimbatore -- 291999
Keywords: Digital twin; FPGA; Real-time simulator